Neglected tropical disease as a 'biographical disruption': Listening to the narratives of affected persons to develop integrated people centred care in Liberia. - Laura Dean; Rachel Tolhurst; Gartee Nallo; Karsor Kollie; Anthony Bettee; Sally Theobald (Public Library of Science (PLoS), 2019)
BACKGROUND:Integrated disease management, disability and inclusion (DMDI) for NTDs is increasingly prioritised. There is limited evidence on the effectiveness of integrated DMDI from the perspective of affected individuals and how this varies by differing axes of inequality such as age, gender, and disability. We used narrative methods to consider how individuals' unique positions of power and privilege shaped their illness experience, to elucidate what practical and feasible steps could support integrated DMDI in Liberia and beyond. METHODS:We purposively selected 27 participants affected by the clinical manifestations of lymphatic filariasis, leprosy, Buruli Ulcer, and onchocerciasis from three counties in Liberia to take part in illness narrative interviews. Participants were selected to ensure maximum variation in age, gender and clinical manifestation. Narrative analysis was grounded within feminist intersectional theory. FINDINGS:For all participants, chronic illness, morbidity and disability associated with NTDs represented a key moment of 'biographical disruption' triggering the commencement of a restitution narrative. Complex health seeking pathways, aetiologies and medical syncretism meant that adoption of the 'sick role' was initially acceptable, but when the reality of permanency of condition was identified, a transition to periods of chaos and significant psycho-social difficulty occurred. An intersectional lens emphasises how biographical disruption is mediated by intersecting social processes. Gender, generation, and disability were all dominant axes of social inequity shaping experience. SIGNIFICANCE:This is one of the first studies to use narrative approaches to interrogate experience of chronic disabling conditions within LMICs and is the only study to apply such an analysis to NTDs. The emotive power of narrative should be utilised to influence the value base of policy makers to ensure that DMDI strategies respond holistically to the needs of the most marginalised, thus contributing to more equitable people-centred care.